ANALYSIS OF PHYSICAL AND MECHANICAL PROPERTIES OF REFRACTORY BASALT YARN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study examines the physical and mechanical properties of refractory basalt yarn, focusing on its application in the textile industry to produce high fire-resistant knitted fabrics. The research highlights the development of 35-tex basalt yarn, derived from volcanic rock, and its testing under both untwisted and twisted conditions. Key parameters such as thread variation (CV), deformation (EL), breaking strength (RKM), and twist count (K) were analyzed. The study also explores the production of three variants of knitted fabrics using a 7th-class flat double-needle knitting machine. The results demonstrate the potential of basalt yarn in creating durable, flame-resistant fabrics suitable for specialized outerwear, contributing to advancements in textile material science.